Business statistics : for management and economics - Daniel, Wayne W; Terrell, James C (Houghton Mifflin Company, 1989)
Business Statistics for Management and Economics is an application-oriented text providing students with a solid grounding in statistical theory and allowing them to make the most of data analysis techniques. Students learn through examples and applications of the most common statistical concepts and techniques used in business, economics and management.
Keywords: ekonomie, ekonomika, ekonomika zdravotnictví; obchod; statistika